The Effect of Financial Ratio in Determining Company Value: (Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period) - Wulan Mawarti; Dimas Angga Negoro; Tantri Yanuar Rahmat Syah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The main objective of company management is to maximize shareholder wealth, namely increasing the company's share price, so efforts are needed to increase the company's share price through increasing company value. Various ratios can be used to evaluate a bank's ability to make capital structure decisions based on its asset structure and firm value, including Return on Equity (ROE), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Non-performing loan (NPL). This research gap is filled because no one has previously investigated the effect of this ratio on banking companies listed on the IDX between 2015 and 2019. The research method is quantitative; independent variables are ROE, LDR, CAR, company size, and non-performing loans. The dependent variable is the firm value of banking companies listed on the Indonesia Stock Exchange from 2015 to 2015-2019 with a population of 49 banks, purposive sampling, descriptive analysis, and hypothesis testing using multiple linear regression analysis in SPSS 25. The hypothesis proposed is that ROE, LDR, and CAR ratios have a positive effect on firm value. On the other hand, the ratio of LDR and NPL is detrimental to Firm Values. The results of the Simultaneous Test (F-Test) show an F value of 13.047 and a significance level of 0.000, meaning that the calculated F value > F table (0.05; 5; (225-5) = 2.255) and a level of <0.05 indicates that there is a simultaneous effect of ROE, LDR, CAR, firm size, and NPL to solid value. This study shows that financial ratios can be used to describe a company's ability to meet short-term obligations, especially strategic decision-makers involving investment, profitability, and capital.